Lipid accumulation product is a better predictor of metabolic syndrome in Chinese adolescents: a cross-sectional study - Chen, Zi-yi; Liu, Lei; Zhuang, Xu-xiu; Zhang, Yi-cong; Ma, Ya-nan; Liu, Yang; Wen, De-liang (Frontiers in Endocrinology, 2023)
Aim: Confirm and compare the associations between non-traditional lipid profiles and MetS in Chinese adolescents, determine the lipid parameter with better predictive potential, and investigate their discriminatory power on MetS. Methods: Medical measurements were undergone among a total sample of 1112 adolescents (564 boys and 548 girls) aged from 13 to 18 years. Univariate and multivariate logistic regression analyses were applied for assessing the relationships between the levels of traditional/non-traditional lipid profiles and MetS. We performed Receiver Operating Characteristic (ROC) analyses to mensurate the effectiveness of lipid accumulation product (LAP) on the prediction of MetS. Meanwhile, areas under the ROC curve and the cut-off values were calculated for MetS and its components. Results: Univariate analysis showed that all our lipid profiles were closely associated with MetS (P < 0.05). LAP index showed the closest association with MetS than the other lipid profiles. Additionally, ROC analyses indicated that the LAP index showed sufficient capabilities to identify adolescents with MetS and its components. Conclusions: The LAP index is a simple and efficient predictor to identify individuals with MetS in Chinese adolescents, with the optimal cut-off values at 38.025 for boys and 28.91 for girls.